STUDY ON THE PREFERENCE OF CUSTOMERS TOWARDS CASUAL RESTAURANT’S REWARD PROGRAM IN KOTA KINABALU, SABAH - R. H. Leoneeta , L. T. Ming, & D. K. Rafidzah (International Journal of Research Science and Management, 2019)
This study aimed to identify customer’s preference for time rewards (immediate or delayed/accumulated) and their preference for types of rewards (monetary or non-monetary) as well as to determine the factors that motivate consumers of joining casual restaurant reward programs. Study was conducted on 400 respondents from Kota Kinabalu. Results showed that the majority of respondents prefer immediate reward compared to delayed or accumulated rewards. Majority respondents were also found to favor monetary rewards as compared to non-monetary rewards. Monetary savings and quality are identified as the main factors which motivates consumer to join casual restaurant reward program while exploration was found to be the least important factor. This study is able to help the restaurant industry that is working to build reward program for their restaurant.